Frontispiz: Efficient Asymmetric Biomimetic Aldol Reaction of Glycinates and Trifluoromethyl Ketones by Carbonyl Catalysis. (30th August 2021) - Cheng, Aolin; Zhang, Liangliang; Zhou, Qinghai; Liu, Tao; Cao, Jing; Zhao, Guoqing; Zhang, Kun; Song, Guanshui; Zhao, Baoguo
Abstract : Organokatalyse In der Zuschrift auf S. 20328 beschreiben Guoqing Zhao, Baoguo Zhao et al. eine hoch effiziente asymmetrische biomimetische Aldolreaktion von Glycinaten und Trifluormethylketonen mittels Carbonyl‐Katalyse.